2006
DOI: 10.1002/jnr.20877
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-L-carnitine-induced up-regulation of heat shock proteins protects cortical neurons against amyloid-beta peptide 1–42-mediated oxidative stress and neurotoxicity: Implications for Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by loss of memory and cognition and by senile plaques and neurofibrillary tangles in brain. Amyloid-beta peptide, particularly the 42-amino-acid peptide (Abeta(1-42)), is a principal component of senile plaques and is thought to be central to the pathogenesis of the disease. The AD brain is under significant oxidative stress, and Abeta(1-42) peptide is known to cause oxidative stress in vitro and in vivo. Acetyl-L-carnitine (ALC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 64 publications
3
85
0
Order By: Relevance
“…We previously have shown that ALCAR protected neurons against Aβ (1-42)-induced oxidative stress, mitochondrial dysfunction and neurotoxicity, in primary cortical cultures (51). In the present study, we show that ALCAR+LA pretreatment, protected against HNEinduced oxidative stress (protein oxidation and lipid-peroxidation), mitochondrial dysfunction and neurotoxicity in cortical cultures.…”
Section: Discussionsupporting
confidence: 72%
“…We previously have shown that ALCAR protected neurons against Aβ (1-42)-induced oxidative stress, mitochondrial dysfunction and neurotoxicity, in primary cortical cultures (51). In the present study, we show that ALCAR+LA pretreatment, protected against HNEinduced oxidative stress (protein oxidation and lipid-peroxidation), mitochondrial dysfunction and neurotoxicity in cortical cultures.…”
Section: Discussionsupporting
confidence: 72%
“…Evidence for activation of the oxidative stress pathway starts from CA3 sector in the hippocampus and leads to a progressive hippocampal apoptosis and atrophy (Cruz-Sánchez et al 2010). The dual effect of Hsps in execution of Aβ-induced, oxidative stress-mediated apoptosis has been demonstrated (Abdul et al 2006). Here, we observed that Aβ-depleted GSH, an indicator of oxidative stress, caused a mild increase in Hsp90 and Hsp70 levels.…”
Section: Discussionmentioning
confidence: 53%
“…One such cellular stress response is heat shock proteins, which protect cells from various forms of stress. Heat shock proteins serve as molecular chaperones which exist in various types including Hsp32 (also known as heme oxygenase-1), Hsp60, and Hsp72 all of which have been shown to play a protective role in the brain in regard to oxidative stress 31 . Heat shock cognate (Hsc71), an isoform of Hsp73, is employed by the cell as a primary defense against unfavorable conditions.…”
Section: Resultsmentioning
confidence: 99%